EKUITAS MEREK HAND BODY LOTION CITRA DI KALANGAN MAHASISWI FAKULTAS EKONOMI UNIVERSITAS MUHAMMADIYAH MALANG - Lina Ariani, Jondry. A. Hetharie, (IQTISHODUNA, 2011)
Research is a descriptive study with survey method. It is titled with “The Analysis of The Elements of Citra Hand Body Lotion’s Brand Equity (A Survey over The Female Students of Faculty of Economic, Malang University of Muhammadiyah).The objective of research is to understand the customer’s awareness rate on Citra Hand Body Lotion, to acknowledge what attributes are related to Citra Hand Body Lotion which are associated with the brand image, to examine the customer’s perceived quality of Citra Hand Body Lotion, and to observed the customer loyalty rate of Citra Hand Body Lotion. It is indicated that top of mind for Citra Hand Body Lotion’s is counted for 89 or 89 %. Result of brand loyalty variable shows that respondent may be classified as switcher. Cochran Test determines that the association which is producing the brand image of Citra Hand Body Lotion is the attribute of softening and humidifying benefits. Result of the analysis of importance-performance diagram insists that the indicator to protect skin from UV ray can be entered to Quadrant I meaning that it has high importance but with low performance of Citra Hand Body Lotion.